Strategi Penetapan Harga Produk dan Jasa bagi UMKM untuk Meningkatkan Daya Saing dan Keberlanjutan Usaha - Widiastuti, Maria; Riorini, Sri Vandayuli; Sirait, Koramen Haulian; Dirdia, Ringke; Widiasmara, Sharoh (PT. Cendekia Sapta Indonesia, 2025)
This community service program aimed to enhance MSME owners’ understanding of product and service pricing strategies to improve competitiveness and business sustainability. The activity was conducted online during the Covid-19 pandemic, involving participants from the Integrated Indonesian MSME Council in West Jakarta. The training covered various pricing approaches such as cost-plus pricing, competitive pricing, penetration pricing, and value-based pricing. Evaluation was carried out through pre-tests, post-tests, and reflective discussions. The results indicated a significant improvement, with 75% of participants able to understand the basic principles of pricing strategies after the training, compared to only 30% beforehand. Participants also reported that the training was highly relevant in increasing business income and strengthening product competitiveness in the market. This program demonstrates that case-based training can effectively improve MSME marketing literacy and promote more measurable business practices.